THE CONCEPT OF "ANTOCOMPONENT" IN LINGUISTICS (Web of Technology: Multidimensional Research Journal, 2025)
The emergence of new terms to express linguistic units is a natural result of the continuous development of linguistic science. As language is a dynamic and multifaceted phenomenon, traditional terminology often fails to capture the complexity of newly discovered linguistic forms and functions. With the expansion of linguistic research into areas such as cognitive linguistics, pragmatics, and sociolinguistics, scholars require more precise concepts to describe novel aspects of meaning, structure, and usage. Moreover, the rise of digital communication and cross-linguistic studies has revealed new types of linguistic data that cannot be adequately explained by earlier terms. Therefore, the creation of new linguistic terminology ensures clarity, accuracy, and adaptability in describing the ever-evolving nature of language.